From Unasur to Prosur: dynamics of regional ideological convergences - Granja Hernández, Lorena (2020)
The purpose of this paper is to analyze South American regionalism from the perspective of ideological convergence and divergence between the determinant actors at times considered as critical junctures, when institutions and normative arrangements were modified and created, which subsequently have important consequences for the configuration of the regional scenario. Thus, the ideological rearrangement in the governments of the region that took place as of 2015, determined the change in the regional political scenario, this juncture led to the disruption of Unasur and the emergence of Prosur. Firstly, we analyze the case of the Union of South American Nations (Unasur) as one of the examples of the emergence of, as denominated, post-liberal regionalism; its decline; as a result of changes in the ideological spectrum of governments in the region; and the prospects for its substitution by a new mechanism that is rhetorically marked by a right-wing discourse, the Forum for the Progress of South America (Prosur). We characterize post-liberal regionalism from its contrast with open regionalism, both concepts widely considered by scholars, and then, we look at the constitution and evolution of the Unasur project as a case in which the ideological aspect of integration was one of the determining variables of its performance, as well as its decline. With its emptying, it is intended to account for the ideological change in the direction that regionalism would take in South America in recent years and the possible new normative frameworks (Prosur) that would support it.